2022
DOI: 10.3389/fevo.2022.998945
|View full text |Cite
|
Sign up to set email alerts
|

Space-time perception and behavioral response of farmers to climate change: Evidence from Sichuan Province, China

Abstract: It is of great significance for global environmental governance to guide farmers to effectively perceive climate change. Based on the survey data of 540 farmers in Sichuan Province, China, this study used binary Logit model and Multinomial Logistic Regression model to explore the effects of farmers’ space-time perception of climate change and their interaction effects on farmers’ adaptation behavior to climate change. The results showed that: (1) 88.51% of farmers took adaptation measures to climate change, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…This corroborates the findings of the previous studies that the residents' perceptions of the effects of global warming and climate change are global, as demonstrated by Katz et al (2020) and Berger et al (2019). The public's spatial psychological distance and spatial perception of climate change are global (Busch and Ayala Chávez, 2022;Ma et al, 2022). The implementation of policies to reduce greenhouse pollution will only show long-term benefits at the global level (Sun et al, 2022).…”
Section: Results and Analysissupporting
confidence: 89%
See 3 more Smart Citations
“…This corroborates the findings of the previous studies that the residents' perceptions of the effects of global warming and climate change are global, as demonstrated by Katz et al (2020) and Berger et al (2019). The public's spatial psychological distance and spatial perception of climate change are global (Busch and Ayala Chávez, 2022;Ma et al, 2022). The implementation of policies to reduce greenhouse pollution will only show long-term benefits at the global level (Sun et al, 2022).…”
Section: Results and Analysissupporting
confidence: 89%
“…Many studies have shown this temporal preference for residents' spatial psychological distance to be distant from their temporal psychological distance, such as those by Keller et al (2022), Gubler et al (2019), Wang et al (2019), and Lee and Barnett (2020). However, it has also been found that residents are more sensitive to spatial psychological distance than temporal psychological distance (Ma et al, 2022). This may be due to differences in age and occupation of the participants in different studies; for example, the latter study group included farmers who were more closely associated with the climate (Ma et al, 2022).…”
Section: Influencing Factorsmentioning
confidence: 96%
See 2 more Smart Citations
“…In recent years, a growing number of scholars have realized that farmers are often rational in specific climate change risk scenarios. Farmers will take adaptive actions in combination with their own capabilities while pursuing maximum benefits [40,41]. Most farmers realize that the extreme weather caused by climate change has caused crop yield reduction, which has greatly hindered their production and livelihoods, and increased the uncertainty of agricultural input and output [42].…”
Section: Theoretical Analysis and Research Assumptionsmentioning
confidence: 99%